Electrocatalyst Screening on a Massive Array of Closed Bipolar Microelectrodes. Issue 10 (8th October 2021) - Anderson, Todd J.; Defnet, Peter A.; Cheung, Robin A.; Zhang, Bo
Abstract : Herein, we report the use of a massive array of bipolar ultramicroelectrodes (UMEs) in conjunction with electrochemiluminescence (ECL) imaging as a novel electroanalytical platform for rapid screening of electrocatalysts. Following our recent work on carbon bipolar UME arrays, we have developed asymmetric carbon-gold bipolar UME arrays where each carbon UME is coated by a thin gold film on one side. To generate large quantities of compositionally varied electrocatalyst samples, a radial gradient of catalytic metal is electrodeposited on the surface of these UME arrays by delivering a plume of metal salt solution to the array surface with a micropipette while the entire array is biased at a reducing potential. We then utilize these bipolar UME arrays to investigate the impact of varied Ni(OH)2 coverage on the catalytic activity for hydrogen evolution reaction (HER) of an Au surface in alkaline solution, with the catalytic performance of the modified Au being confirmed to exhibit a peak-shaped dependence on increasing Ni(OH)2 coverage. Our future work will expand this unique platform to enable the screening of various metal alloys by incorporating additional micropipettes for delivering multiple metal salts to the array during the gradient electrodeposition process.